Sepsis-induced modulation of long-term potentiation induced by theta burst stimulation in the rat hippocampus - Kakizaki, Ryuichiro; Narimatsu, Eichi; Kasai, Takehiko; Nomura, Kazuhito (Frontiers in Neuroscience, 2023)
We investigated the influences of sepsis on central synaptic plasticity in vitro. Cecal ligation and puncture (CLP) was performed by creating rat sepsis models, which were divided into early and late sepsis groups (8 and 16 h after CLP, respectively). In the CA1 of the rat hippocampal slices, orthodromically elicited population spikes (PSs) and field excitatory postsynaptic potentials (fEPSPs) were simultaneously recorded, and their long-term potentiation (LTP) was induced by theta burst stimulation (TBS). TBS induced LTPs of PSs and fEPSPs in all groups. In the sham and early sepsis groups, there was no significant difference in LTPs between PSs and fEPSPs. However, in the late sepsis group, the LTP of PSs was greater than that of fEPSPs (p < 0.05) and was greater than the LTPs of PSs in the sham and early sepsis groups (p < 0.05). Superoxide dismutase, administered immediately before CLP, inhibited the enhancement of LTP in PS, as observed in the late sepsis group. The initial rapid potentiation component of LTP in fEPSPs was suppressed or reduced in all groups that underwent CLP. The results indicate that CLP-induced sepsis modulates hippocampal synaptic plasticity, depressing excitatory synaptic transmissions and facilitating somatic excitability, which is induced by septic oxygen superoxide.